2017
DOI: 10.3390/nu9050456
|View full text |Cite
|
Sign up to set email alerts
|

Under 5 Energize: Tracking Progress of a Preschool Nutrition and Physical Activity Programme with Regional Measures of Body Size and Dental Health at Age of Four Years

Abstract: To reduce weight gain and encourage healthy eating including reduced sugar intake, Under 5 Energize (U5E) was introduced to 121 early-childhood-centres in the Waikato region of New Zealand in July 2013. Using anonymized data collected from January 2013 to September 2016 through free physical assessments of all 4-year-olds provided by the NZ Ministry of Health, the prevalence of obesity and dental decay children measured in the Waikato region was examined. Data were divided into four periods representing pre-im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…Many of the studies reviewed reported improvements in nutrition-related outcomes, although methodological quality varied. Three interventions with a focus on reducing sugar-sweetened beverages in children’s settings demonstrated statistically significant improvements in health outcomes for Indigenous children, including dental health 25 31 and insulin sensitivity, 43 suggesting a pro-equity effect. Although most school-based interventions did not change BMI, those studies that evaluated BMI as an outcome were of relatively short duration.…”
Section: Discussionmentioning
confidence: 99%
“…Many of the studies reviewed reported improvements in nutrition-related outcomes, although methodological quality varied. Three interventions with a focus on reducing sugar-sweetened beverages in children’s settings demonstrated statistically significant improvements in health outcomes for Indigenous children, including dental health 25 31 and insulin sensitivity, 43 suggesting a pro-equity effect. Although most school-based interventions did not change BMI, those studies that evaluated BMI as an outcome were of relatively short duration.…”
Section: Discussionmentioning
confidence: 99%
“…In the B4SC data set, deprivation (based on the location of the child's home) is reported on an integral scale of 1 to 5, with 1 being the least deprived and 5 the most deprived. Details of measurement protocols have been reported previously 12 and are mandated by the Ministry of Health. 13 From the initial set of 281,680 records, we removed any that were incomplete and/or the WHO z-score for height, weight, or implausible BMI z-scores that were <− 3 or >+ 4.…”
Section: Methodsmentioning
confidence: 99%
“…We have previously analysed regional data from the national and free New Zealand Before School Check (B4SC) and reported that between January 2013 and September 2016, there was no observable change in obesity prevalence. 12 However, for the children attending the U5Ee centres the prevalence of visible dental decay decreased, with the decrease particularly marked for the indigenous Māori children, in whom the prevalence declined from 19 to 16% (P for trend 0.02). It is important to document the time trend of the impact of U5E on overweight/obesity and dental decay particularly from 2015 onwards when the U5E intervention was fully implemented in all selected preschools (n = 121).…”
Section: Introductionmentioning
confidence: 94%
“…There is also limited inclusion of nutrition in teacher training across the ECE sector in New Zealand and nutrition education opportunities for ECE staff are sparse ( 49 ) . A possible way to achieve more professional development in nutrition for ECE staff would be to incorporate aspects of the Heart Foundation’s HHA into widespread teacher training and professional practice, and/or the expansion of health-promotion programmes such as the HHA or Under 5 Energize ( 50 ) , which promote knowledge transfer to staff. The HHA is currently voluntary and targeted to early education services in areas of high deprivation ( 51 ) .…”
Section: Discussionmentioning
confidence: 99%